Potential use of TG68 - A novel thyromimetic - for the treatment of non-alcoholic fatty liver (NAFLD)-associated hepatocarcinogenesis - Caddeo, Andrea; Serra, Marina; Sedda, Francesca; Bacci, Andrea; Manera, Clementina; Rapposelli, Simona; Columbano, Amedeo; Perra, Andrea; Kowalik, Marta Anna (Frontiers in Oncology, 2023)
Several lines of evidence suggest that the thyroid hormone signaling pathway is altered in patients with NAFLD and that pharmacological strategies to target the thyroid hormone/thyroid hormone nuclear receptor axis (TH/THR) in the liver may exert beneficial effects. In this study, we investigated the effect of TG68, a novel THRβ agonist, on rat hepatic fat accumulation and NAFLD-associated hepatocarcinogenesis. Male rats given a single dose of diethylnitrosamine (DEN) and fed a high fat diet (HFD) were co-treated with different doses of TG68. Systemic and hepatic metabolic parameters, immunohistochemistry and hepatic gene expression were determined to assess the effect of TG68 on THRβ activation. Irrespectively of the dose, treatment with TG68 led to a significant reduction in liver weight, hepatic steatosis, circulating triglycerides, cholesterol and blood glucose. Importantly, a short exposure to TG68 caused regression of DEN-induced preneoplastic lesions associated with a differentiation program, as evidenced by a loss of neoplastic markers and reacquisition of markers of differentiated hepatocytes. Finally, while an equimolar dose of the THRβ agonist Resmetirom reduced hepatic fat accumulation, it did not exert any antitumorigenic effect. The use of this novel thyromimetic represents a promising therapeutic strategy for the treatment of NAFLD-associated hepatocarcinogenesis.